Epidemiology of maternal depression, risk factors, and child outcomes in low-income and middle-income countries - Gelaye, Bizu (Lancet Psychiatry, 2016)
Maternal depression, a non-psychotic depressive episode of mild to major severity, is one of the major contributors of pregnancy-related morbidity and mortality. Maternal depression (antepartum or post partum) has been linked to negative health-related behaviours and adverse outcomes, including psychological and developmental disturbances in infants, children, and adolescents. Despite its enormous burden, maternal depression in low-income and middle-income countries remains under-recognised and undertreated. In this Series paper, we systematically review studies that focus on the epidemiology of perinatal depression (ie, during antepartum and post-partum periods) among women residing in low-income and middle-income countries. We also summarise evidence for the association of perinatal depression with infant and childhood outcomes. This review is intended to summarise fi ndings from the existing literature, identify important knowledge gaps, and set the research agenda for creating new generalisable knowledge pertinent to increasing our understanding of the prevalence, determinants, and infant and childhood health outcomes associated with perinatal depression. This review is also intended to set the stage for subsequent work aimed at reinforcing and accelerating investments toward providing services to manage maternal depression in low-income and middle-income countries.